Equilibrium, Kinetic, and Thermodynamic Study of Removing Methyl Orange Dye from Aqueous Solution Using Zizphus spina-christi Leaf Powder - Fadya F. Mohammed (مجلة بغداد للعلوم, 2023)
In this study, Zizphus spina-christi leaf powder was applied for the adsorption of methyl orange. The effect of different operating parameters on the Batch Process adsorption was investigated such as solution pH (2-12), effect of contact time (0-60 min.), initial dye concentration (2-20 mg/L), effect of adsorbent dosage (0-4.5 g) and effect of temperature (20-50ᵒC). The results show a maximum removal rate and adsorption capacity (%R= 23.146, qe = 2.778 mg/g) at pH = 2 and equilibrium was reached at 40 min. The pseudo- second-order kinetics were found to be best fit for the removal process (R2 = 0.997). Different isotherm models (Langmuir, Freundlich, Dubini-Radushkevich,Temkin)  were applied in this study and the adsorption process was found to fit Dubinin-Radushkevich  isotherm (R2 = 0.970). The thermodynamic parameters:  ∆Gº, ∆Hº, ∆Sº were also invested, the results indicate the process to be exothermic (∆Hº = -100.933 kJ/mole), non-spontaneous, and more feasible at lower operating temperatures, with a decrease in the randomness at the solid-liquid interface (∆Sº = - 0.370 kJ/mole.K)